Measuring host finding capacity and arrestment of natural enemies of the cassava mealbug, Phenacoccus manihoti, in the field - Neuenschwander, Peter; Ajuonu, O. (Wiley, 1995)
In uninfested fields, 80 cassava tips were artificially infested with 0, 1, 2, 4, 8, 16, 32, or 64 third instars, and 20 or 100 eggs of cassava mealybug, Phenacoccus manihoti Matile‐Ferrero (Hom., Pseudococcidae). Another 80 uninfested tips served as a control. Tips were arranged in a circle of 28 m diameter, in the centre of which the following exotic natural enemies of P. manihoti were released: Apoanagyrus (Epidinocarsis) lopezi De Santis and A. diversicornis (Howard) (Hym., Encyrtidae), Hyperaspis notata (Mulsant) and Diomus hennesseyi Fürsch (Col., Coccinellidae), and others. This experiment was repeated six times. During the 4–14 days following release, all experimental tips were inspected at two‐hour intervals during each day and the presence of exotic as well as indigenous natural enemies, like Exochomus troberti Mulsant (Col., Coccinellidae), ants and spiders was noted. The experiment was repeated six times measured the aggregative response by the natural enemies to different host densities, achieved through host attractance and arrestment. All exotic natural enemies, except the males of Apoanagyrus spp., were fast attracted to the host colonies. As compared to the control tips, they concentrated on the infested tips about 50‐fold for the two Apoanagyrus spp. and 10 to 20‐fold for the exotic coccinellids. By contrast, non‐coevolved indigenous coccinellids, as well as generalist predators like ants and spiders were attracted to the infested tips only 2 to 5‐fold. A. lopezi responded best to different host densities, followed by A. diversicornis and the coccinellids, followed by ants and spiders. None of the parasitoids or predators was particularly attracted to egg masses. These results correspond closely to the known efficiencies of these natural enemies, A. lopezi standing out among all candidates. The results of such aggregation studies are compared with those of life‐table studies.